Komparasi Teori Marketing Politik 4p Menurut Niffenegger dan 3p Menurut Adman Nursal - Sutrisno Sutrisno; Neneng Yani Yuningsih; Leo Agustino (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2018)
This study describe, as well as analyze Comparative Political Marketing Theory 4p According Niffenegger and 3p According to Adman Nursal. The first is the marketing of politics that uses the theory of market approach strategy (Nursal 2004) called 3P terms are Pull Marketing, Push marketing, and Pass marketing. Then the second is marketing politics using marketing mix or marketing mix (Niffenneger 1989), known as 4P, product, promotion, price and place. This article will discuss the differences and similarities of both theories. Political marketing has been used as a winning strategy. Many of these strategies have their own to be well received by the public. Marketing concepts adapted in politics used to improve the efficiency and effectiveness of ideological transfers and work programs, from contestants to the public in a campaign. In this study researchers used literature study method. The literature study used library data collection methods, reading and recording, as well as managing research materials. The results of the study show that both theories can complement each other in the field. Niffenneger's theory for understanding political marketing maps. While Adman Nursery's theory is more about candidate promotion techniques at the grassroots.